2020
DOI: 10.1136/annrheumdis-2020-218582
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase inhibitor significantly improved rash and muscle strength in juvenile dermatomyositis

Abstract: A typical case of a girl >25 kg who received an initial dose of 5 mg twice daily of Janus kinase inhibitor (JAKi) but required the maximum dose of 7.5 mg twice daily. She received this dose for 6 months, and the dose was gradually tapered. In the meantime, glucocorticoids were also tapered, and the patient showed an increased growth rate. (A) The typical skin lesions before treatment with JAKi. (B) Those lesions had mostly disappeared after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…They have shown efficacy in adult rheumatic conditions and are included in clinical guidelines of rheumatoid arthritis ( 15 ), psoriatic arthritis ( 16 ), ankylosing spondylitis ( 17 ). Currently, the experience of JAK-inhibitors in the pediatric population is scarce and limited to a single randomized placebo-controlled study in JIA and several studies in small groups of patients with immune-mediated diseases ( 18 , 19 ). The largest randomized, double-blind, placebo-controlled withdrawal study of tofacitinib in JIA showed that patients with polyarticular course of JIA treated with tofacitinib have significantly lower rate of disease flare at 44 weeks compared to placebo-group (29% vs 52.9%, p=0.0031).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown efficacy in adult rheumatic conditions and are included in clinical guidelines of rheumatoid arthritis ( 15 ), psoriatic arthritis ( 16 ), ankylosing spondylitis ( 17 ). Currently, the experience of JAK-inhibitors in the pediatric population is scarce and limited to a single randomized placebo-controlled study in JIA and several studies in small groups of patients with immune-mediated diseases ( 18 , 19 ). The largest randomized, double-blind, placebo-controlled withdrawal study of tofacitinib in JIA showed that patients with polyarticular course of JIA treated with tofacitinib have significantly lower rate of disease flare at 44 weeks compared to placebo-group (29% vs 52.9%, p=0.0031).…”
Section: Discussionmentioning
confidence: 99%
“…Ding and colleges reported successful management of 24/25 children refractory JDM with JAK-inhibitors (18 patients were treated with ruxolitinib and seven patients with tofacitinib). Complete skin rash resolution was achieved in 67% cases, 28% of patients discontinued steroids, and 7/10 patients with decreased muscle strength had improved CMAS score ( 18 ). The prospective, open-label clinical trial of tofacitinib in 10 adults with refractory dermatomyositis demonstrated efficacy of JAK-inhibitors in all patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, advances in the understanding of the immunopathology and genetics in JDM may help to specify new treatment approaches, especially when conventional therapy is not successful. An upregulated type 1 interferon signature is strongly associated with JDM, which could present the possibility for the treatment of most severe cases with JAK inhibitors ( 17 , 18 ). However, the safety and efficacy of this therapy still need to be studied in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…JAK inhibitors competitively inhibit the ATP binding site on JH1. [5][6][7] Tofacitinib (CP-690550), formerly known as tasocitinib, is the first FDA-approved JAK inhibitor for treatment of an autoimmune disease, and was initially studied as an antirejection agent in organ transplantation. Tofacitinib primarily inhibits JAK1 and JAK3, which are found on T cells, B cells, natural killer cells and mast cells.…”
Section: Biology Of Tofacitinibmentioning
confidence: 99%